Effect Of Animal-Fat Supplementation To The Diet Of Large White Yorkshire Pigs On Energy Utilization (Applied Biological Research, 2020)
The study was conducted to assess the effect of animal-fat supplementation  on energy utilization in Large White Yorkshire (LWY) pigs fed with corn  soya-based ration as per the requirements of NRC (2012). Twenty weaned  piglets were randomly divided into two groups and allotted to one of the  wo dietary treatments i.e. control ration (as per NRC, 1998) and ration  supplemented with animal fat @ 5%. A digestibility trial was conducted  following total collection method and gross energy was estimated using  bomb calorimeter. The results revealed that gross energy of feed and faeces  were 4144, 4410 and 4102, 4090 kcal kg-1, respectively, for control and  animal feed supplemented treatments. The gross energy converted as  digestible energy was 85.8 and 87.3% and the calculated digestible energy  of feed was 3558.1 and 3848.8 kcal kg-1for the respective groups. The result  showed that the animal-fat supplementation (5%) increased the efficiency  of energy utilization in growing LWY pigs.
Keywords: Animal fat; energy utilization; feeding efficiency; pigs